Evaluation Of Implementation Of 2013 Curriculum In Learning Outcomes Perspective For Sport And Health Physical Education - Pangestu, Eggi; Hartati, Hartati; Sumarni, Sri (CV. Inara, 2022)
This research is motivated by the strategic policies of State Senior High School 6 Palembang in implementing the 2013 curriculum within 9 years. Based on this, to find out more about the level of implementation of the 2013 curriculum in terms of the aspect of learning achievement of Physical Education in Sports and Health (PEH) in the context of the 2013 curriculum in an objective and factual manner. This study aims to evaluate the implementation of the 2013 curriculum in terms of learning outcomes for physical education, sports and health. The research method used is mixed research with the CIPP model evaluation method (context, input, process, product). Research data was obtained through observation, interviews, and questionnaires. The data collected were analyzed using descriptive qualitative and percentages. The results showed that the evaluation of the implementation of the 2013 curriculum in terms of PEH learning outcomes was good. This can be seen from the evaluation of the PEH curriculum in the context of the 2013 curriculum in the form of the legal basis for the Regulation of the Minister of Education and Culture Number. 22 of 2016, and has carried out intensive socialization with school residents. The input evaluation shows that the implementation has been supported by a good quality curriculum. Process evaluation shows that the school can organize the implementation of the preparation of teaching preparation by the signs set out in the guidelines for preparing learning plans. While the product evaluation shows qualitatively in detail according to indicators, where knowledge and skills, data findings are also strengthened by observations that the learning outcomes target and graduate qualification criteria. In addition, the results of observations and responses of teachers and students are very high.